Best original research presented at the 23rd European Congress on Gynaecological Oncology—Best of ESGO 2022. Issue 2 (15th December 2022) - Kacperczyk-Bartnik, Joanna; Bizzarri, Nicolò; Angeles, Martina Aida; Theofanakis, Charalampos; Shushkevich, Alexander B; Strojna, Aleksandra Natalia; Pletnev, Andrei; Nikolova, Tanja; Ledermann, Jonathan; Vergote, Ignace
Abstract : Best of ESGO 2022 includes a selection of best original research presented during the 23rd European Congress on Gynaecological Oncology between October 27 and 30, 2022 in Berlin. Out of 1107 submitted abstracts, authors of studies which obtained the highest scores in a blinded review process were invited to present their results during four oral sessions, young investigators session, and oral poster sessions. By means of this publication, we aim to provide readers with an overview of the best quality research presented at the European Society of Gynaecological Oncology (ESGO) 2022.